2021
DOI: 10.1039/d0sc06623k
|View full text |Cite
|
Sign up to set email alerts
|

Chemoproteomic profiling of kinases in live cells using electrophilic sulfonyl triazole probes

Abstract: Sulfonyl-triazole probes modified with a kinase recognition element are developed for live cell activity-based profiling to identify tyrosine sites located in catalytic and regulatory domains that are important for kinase function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 67 publications
1
27
0
Order By: Relevance
“…We synthesized a sulfonyl–triazole analogue of XO44 named KY-26 for our chemical proteomic studies (Figure ). Our rationale for selecting the triazolide in place of the fluoride as a leaving group is based on our past studies that demonstrated enhanced reactivity at protein sites for sulfur–triazole exchange (SuTEx) compared with sulfur–fluoride exchange (SuFEx) chemistry. , The sulfonyl–triazole reactive group was connected to the 2-aminopyrazole kinase-recognition unit through an amide linkage to increase the electron-withdrawing character of the adduct group for enhanced reactivity of KY-26. Full details of the synthesis and characterization of KY-26 and analogues can be found in Figure S1 and the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We synthesized a sulfonyl–triazole analogue of XO44 named KY-26 for our chemical proteomic studies (Figure ). Our rationale for selecting the triazolide in place of the fluoride as a leaving group is based on our past studies that demonstrated enhanced reactivity at protein sites for sulfur–triazole exchange (SuTEx) compared with sulfur–fluoride exchange (SuFEx) chemistry. , The sulfonyl–triazole reactive group was connected to the 2-aminopyrazole kinase-recognition unit through an amide linkage to increase the electron-withdrawing character of the adduct group for enhanced reactivity of KY-26. Full details of the synthesis and characterization of KY-26 and analogues can be found in Figure S1 and the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the solution reactivity, we compared the activity of KY-26 and XO44 in proteomes using gel-based chemical proteomics. Considering that both SuFEx and SuTEx probes are cell permeable, we performed chemical proteomic studies under live cell treatment conditions. In brief, Jurkat cells were treated with KY-26 or XO44 (5 μM, 30 min, 37 °C) followed by cell lysis, separation of soluble and membrane lysates, and conjugation of a rhodamine tag to the alkyne handle of probe-modified proteins by copper-catalyzed azide–alkyne cycloaddition (CuAAC).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent studies exploring various linkers for appending the alkyne group in SuTEx ABPs support this hypothesis. 168 Another key finding was the near-complete loss of compound reactivity when the AGs of SuTEx ligands were modified with alkyl substituents, which further illustrates the tunable nature of SuTEx for developing protein ligands. 123 By varying aryl substituents on the AG and LG, SuTEx ligands could be tuned for inhibitory activity (475% reduction in enrichment by HHS-482 ABP) against a small subset of tyrosine sites (B7-13 probe-modified sites 123 ).…”
Section: Rsc Chemical Biologymentioning
confidence: 95%
“…For LSF applications, the triazole can also serve as a release linker to develop clickable ABPs for mapping protein targets of drugs and other structurally complex compounds. 168 The success of SuTEx and SuFEx exemplify the growing number of biological and chemical applications that are possible using the sulfur electrophile. The future is promising as synthetic chemists and chemical biologists continue to innovate in covalent chemistry to usher in a 'Su'-nami of new sulfur electrophiles for basic and translational discoveries.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%